Efektivitas Konseling dengan Pendekatan Motivational Interviewing Terhadap Penurunan Depresi pada Pasien Post Stroke Depression - Baiq Nurainun Apriani; Irwan Hadi; Anwar Wardi Warongan; Nana Supriyatna (Holistic Nursing and Health Science, 2018)
Background : Stroke is a serious global health problem, strokes can be threatening and result in morbidity and mortality and increase the length of days of treatment that cause maintenance costs to increase, stroke prevalence increases every year, followed by increased post-stroke depression. Motivational interviewing (MI) is a patient-focused counseling technique designed to help individuals explore and overcome ambivalence in behavior.Purpose : This study aims to determine the effectiveness of counseling with a motivational interviewing approach to reducing depression in post-stroke depression patients in NTB Province Hospital.Method : Quasi Experiment Pre-test design Post-test control group design with a sample of 32 respondents selected by purposive sampling technique.Results: The results of bivariate analysis with paired t test there were significant differences in post-stroke depression in the control group and the intervention group with a value of 0.028, in the intervention group the average depression was 2.25 with a value of 0.000 < α (0.05).Conclusion: Counseling with a motivational interviewing approach is effective in decreasing depression in post stroke depression patients at NTB Hospital. Suggestions for the next researchers can research with different places with more samples and qualitative and quantitative methods (mixed methods) so that research results are more optimal.